The cultural significance of plant-fiber crafts in Southern Africa: a comparative study of Eswatini, Malawi, and Zimbabwe. Issue 4 (2nd October 2021) - Pullanikkatil, Deepa; Thondhlana, Gladman; Shackleton, Charlie
ABSTRACT: Traditional handicrafts made from various plant materials are produced by most cultures around the world. Many originated through symbolic and utilitarian needs that became ritualized through time, thereby gradually attaining greater value as cultural items or symbols rather than solely functional ones. Here we report on a survey of 343 crafters across Eswatini, Malawi, and Zimbabwe in southern Africa regarding the cultural uses and significance of the items they make from wild plant fibers and sell to local communities or tourists. The plant materials used were largely dictated by tradition and local availability and were crafted into a diverse range of products including baskets, mats, brooms, storage containers, hats, fish traps, ornaments, and furniture. Many products had uses and cultural significance at major ceremonies or rituals, such as weddings, funerals, initiation, and divination. The preparation and design of the different crafts were influenced by tradition as well as market demand as indicated by tourist fashions and advice provided by government or non-government agencies to boost income generation from crafts. Although the crafting of cultural objects is increasingly commercialized and subject to the tastes and fashions of tourist markets in the region, the traditional and cultural significance of such artifacts remains widely recognized and valued.